RITUAL PENYEMBUHAN PADA MASYARAKAT SUKU DAYAK DI KALIMANTAN TENGAH DALAM NASKAH KUNO AMIROE - Fadilah, Syila; Rizky, Andi Nunun May; Wahyuni, Erna; Fauziyyah, Nurul Hanna (Smart Education, 2025)
Abstract: This study aims to examine the practices and symbolic meanings within the healing rituals of the Dayak tribe in Central Kalimantan, as documented in the ancient manuscript